2016
DOI: 10.1016/j.jped.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing excessive daytime sleepiness in adolescents

Abstract: Sleep deficit appears to be a reality among adolescents; the results suggest a higher prevalence in students from private schools. Sleep deprivation is associated with older age in adolescents and possible presence of sleep disorders, such as sleep hyperhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…In line with our study, previous studies have also found that older adolescents suffer from higher level of sleepiness. 1 , 29 The reason maybe that adolescents do not prioritize their sleep over social and leisure activities. 30 Furthermore, being a female adolescent was associated with higher scores on ESS-CHAD.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our study, previous studies have also found that older adolescents suffer from higher level of sleepiness. 1 , 29 The reason maybe that adolescents do not prioritize their sleep over social and leisure activities. 30 Furthermore, being a female adolescent was associated with higher scores on ESS-CHAD.…”
Section: Discussionmentioning
confidence: 99%
“…The CASQ was developed to measure daytime sleepiness in adolescents, a typical problem in this population and showed promise in being able to discern between daytime sleepiness and sleep disorders ( 20 ). The CASQ when used in another study by Vilela et al ( 19 ) reported that adolescents with higher scores on the CASQ were associated with the presence of sleep disorders. The SDSC also measures sleep disturbances in children with known or presumed sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The SDSC was further evaluated in a population of 531 adolescents in both public and private schools to measure factors that influence excessive daytime sleepiness in this population ( 18 ). Vilela et al ( 19 ) included items on sleep deficit on the weekends compared to the weekdays to determine a sleep deficit score. This study was a cross-sectional design and may require more longitudinal assessment ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around the world, as many as one-third of all children experience sleep difficulties [2][3][4] , and approximately 15-20% of children report excessive daytime sleepiness 2,5 . In adolescents, rates appear to be similar, if not higher [6][7][8] . Sleepiness can be detrimental to both development and functioning, including cognition and school performance 9 , mood, behavior 10,11 , physical health, and quality of life 2,12,13 .…”
Section: Introductionmentioning
confidence: 84%